Quality Index of Implementation of Religious Moderation Education and Training The Pattern of Distance Learning: Studies in Batch I of the Administration Training Center, Indonesian Ministry of Religion - Matridi Matridi; Idi Warsah (AJIS: Academic Journal of Islamic Studies, 2022)
This study aims to evaluate and analyze the effectiveness of the implementation of education and training in religious moderation for the first generation with the Distance Learning pattern. The method used to measure the quality of the training is the quality index method. This study uses a mixed-method approach between qualitative and quantitative. Quantitative research is used to obtain data and information from the evaluation of the organizers by using a statistical calculation of the quality index. In contrast, qualitative research is used to explore qualitative data in the form of input from respondents regarding training and to describe the results of quantitative data processing. The results of the study show that the implementation of religious moderation education and training with the Distance Learning system is quite adequate, which is obtained from the results of measuring participant satisfaction using the quality index method on three evaluated indicators, namely: First, Participant Evaluation of the Operator; Second, Participant Evaluation of Teachers/Instructors; and Third, evaluating the results of the pre-test and post-test of the participants, after quantitatively calculating the responses of the respondents, the following results were obtained (i) The satisfaction index of the participants to the organizers was in good category with a quality index of 79.33%; (ii) Participant satisfaction index towards instructors/instructors in the Very Good category with a quality index of 97.66 %; (iii) increasing the knowledge and understanding of the training participants by comparing the results of the pre-test and post-test, namely 46.66 % of participants who experienced an increase in scores after the post-test and 53.33 % of participants whose post-test scores were the same as the pre-test scores. Test in the sense that there is no increase in value.